Pengaruh Praktik Total Quality Management (TQM) terhadap Budaya Kualitas dan Daya Saing untuk meningkatkan Kinerja perusahaan (Studi pada Usaha Mikro Percetakan Digital Printing di Kota Pekanbaru-Riau) - Hidayah, Nurul; Indarti, Sri (Jurnal Tepak Manajemen Bisnis, 2016)
The purpose of this research was to know the influences of TQM practices onquality culture and competitiviness to increase company performance (Study on Digitalprinting toward Micro Business in Pekanbaru-Riau. The Population of this research is 179Digital Printing and the researcher used all Digital Printing Industry as samples. Thesampling method used is census method. Structural Equation Modeling (SEM) was usedanalysis of the data and processed with software WarpPLS 3.0.The result of this researchwas significant effect and positive impact on TQM practices on quality culture andcompetitiveness. Quality Culture was positive impact but not significant effect toward thecompany performance. The competitiveness was Positive impact but Not Significant effectin company Performance. TQM value of 4.15, Quality Culture of 4.01, Competitiveness of4.14 and Company performance of 4.25. All of the variables excellent grade intervals.Theresearch recommendation, for all micro digital printing businesses in Pekanbaru-Riau toincrease quality product to produced in order to increase the quality culture of existingprinting. Printing businesses more motivated their employee and participated in training,workshops and unique design to meet customer needs. Printing businesses offeringcompetitive prices and to increase efforts in the competition and followed by deliveringproducts that have quality assurance. The comsumer is the main priority of the company todevelop partnerships with the main stakeholders in the long term for the company tosurvive and thrive with a good performance.